1999
DOI: 10.1017/s0043174500092298
|View full text |Cite
|
Sign up to set email alerts
|

Emergence characteristics of four annual weed species

Abstract: Emergence characteristics, including initial time of emergence, magnitude of emergence, and mean time of emergence, ofAmaranthus rudisSauer,Setaria faberiHerrm.,Eriochloa villosa(Thunb.) Kunth, andAbutilon theophrastiMedik. were studied in central Iowa during the first 3 yr following burial of seed collected and buried in the fall of 1994 or 1995. Although the initial emergence date varied among years, the emergence sequence among species was consistent.Eriochloa villosaand A.theophrastiwere the first species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
175
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(190 citation statements)
references
References 18 publications
13
175
2
Order By: Relevance
“…A mean time of emergence (MTE) value of 41.4 was estimated, which fits into the range (from 30 to 42) observed by Hartzler et al (1999) for this species during three different cropping seasons.…”
Section: Seedling Emergencesupporting
confidence: 88%
See 2 more Smart Citations
“…A mean time of emergence (MTE) value of 41.4 was estimated, which fits into the range (from 30 to 42) observed by Hartzler et al (1999) for this species during three different cropping seasons.…”
Section: Seedling Emergencesupporting
confidence: 88%
“…The phenological behaviour of this weed species in the present trial has been found to be similar to the one observed in the fields of southern and central USA (Hartzler et al 1999) but a bit earlier than the one observed in eastern Canada and northern USA (Warwick and Black 1988) where the flowering starts from late August to September and seed setting occurs from September to October. On the other hand, compared with the observation made in Italy (Cantele et al 1987;Viggiani 1995), the present population shows a slight phenological delay, especially referring to the beginning of emergence.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A primary reason given for this later spring time frame is to ensure the soil is warm enough for more rapid seedling emergence and to avoid the peak emergence period for many summer annual weeds. Previous research determined that weed species exhibit specific patterns of emergence (Hartzler et al 1999;Ogg and Dawson 1984;Stoller and Wax 1973). Hartzler et al (1999) reported that common waterhemp (Amaranthus rudis Sauer), velvetleaf (Abutilon theophrasti Medicus), giant foxtail (Setaria faberi Herrm.…”
mentioning
confidence: 99%
“…Thus, N response should be greater with earlier, rather than later, emergence. Emergence times of species and cohorts (Hartzler et al 1999) may need to be considered when predicting responses to N fertilization.…”
mentioning
confidence: 99%